Fruit and vegetable by-products: Extraction of bioactive compounds and utilization in food biodegradable material and packaging - Ali, Muhammad Qasim; Noormazlinah, Ahmad; Mohd Akmal, Azhar; Mimi Sakinah, Abdul Munaim; Nur Fathin, Ruslan (Maximum Academic Press, 2025)
The detrimental effects of food waste and its by-products on the environment, economy, and society are significant. A sustainable solution to this problem implies the extraction of organic compounds from waste and by-products, with the development of food packaging materials. The use of edible and functional food packaging, food waste, and natural materials offers a sustainable method to minimize waste and plastic consumption. Fruit by-products are particularly valuable food wastes containing beneficial compounds such as polyphenols, vitamins, and minerals. Edible and biodegradable films composed of proteins, polysaccharides, and lipids can be utilized as substitutes for non-biodegradable packaging. By-product compounds are used in biodegradable packaging films because of their accessibility, low cost, eco-friendliness, physical properties, unique sensory and nutritional characteristics, and improved functionality. This study explored the potential applications of biopolymers, packaging materials, edible films, and coatings as substitutes for conventional food packaging. To enhance the physical, mechanical, and antimicrobial properties of packaging systems and improve synthetic and bio-based films enhanced with by-product compounds and their role in biodegradable food packaging.